2016
DOI: 10.1136/bcr-2016-215182
|View full text |Cite
|
Sign up to set email alerts
|

Herpetic cranial polyneuritis mimicking brain stem infarction—an atypical presentation of Ramsay Hunt syndrome

Abstract: An elderly man presented with severe right ear pain and discharge, hoarseness and dysphagia causing significant involuntary weight loss. Extensive investigations by varied specialties only highlighted right vocal cord palsy and right parotid lymphadenitis. Reassessment on transfer to a rehabilitation ward noted clinically subtle right Ramsay Hunt syndrome with multiple lower cranial nerve involvement. We illustrate a case of varicella zoster virus cranial polyneuritis with bulbar symptoms mimicking bulbar stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…These results are not surprising given the degree of swallowing dysfunction previously reported among long‐term OPC survivors in earlier case reports, which suggested that treatment‐related LCNP may play a major role in late RAD and precipitate delayed but extreme oropharyngeal impairment as recorded by MBS studies . These observations also align to numerous reports of significant swallowing dysfunction caused by lower CN deficits among populations (in the absence of head and neck RT) due to traumatic injury, vascular causes, and infection, documented primarily in case reports …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are not surprising given the degree of swallowing dysfunction previously reported among long‐term OPC survivors in earlier case reports, which suggested that treatment‐related LCNP may play a major role in late RAD and precipitate delayed but extreme oropharyngeal impairment as recorded by MBS studies . These observations also align to numerous reports of significant swallowing dysfunction caused by lower CN deficits among populations (in the absence of head and neck RT) due to traumatic injury, vascular causes, and infection, documented primarily in case reports …”
Section: Discussionsupporting
confidence: 82%
“…1,20,21 These observations also align to numerous reports of significant swallowing dysfunction caused by lower CN deficits among populations (in the absence of head and neck RT) due to traumatic injury, vascular causes, and infection, documented primarily in case reports. [41][42][43][44][45] Approximately one-third (28.6%) of patients with late LCNP in our study reported having a feeding tube at the time of survey. High rates of gastrostomy dependence among LCNP cases again support a high prevalence of dysphagia in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of motor action potentials in an NCS and the HBS scale are known as valuable methods for predicting the outcomes of facial palsy [6]. However, swallowing function was restored within a relatively short period, despite severe neural degradation according to the NCS in this case and in a case reported by Shim et al [7] Additionally, the initial severity of RHS-related dysphagia based on the results of a VFSS or a flexible endoscopic evaluation of swallowing (FEES) may not affect prognosis, as in this case and in previous reports [7][8][9][10], in contrast to stroke-related dysphagia. Therefore, electrodiagnostic studies and VDS scores representing the initial severity of dysphagia cannot be used to predict the prognosis of dysphagia in RHS.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, we found that patients who received swallowing rehabilitation therapy recovered swallowing function more quickly compared to those who did not receive therapy. Oral feeding was possible within 2 months through swallowing rehabilitation, including the patient in this case, except for 2 cases in which the patients were more than 80 years old [7][8][9][10]. Elderly patients tend to exhibit greater loss of function, resulting in a difficult recovery [8], and severe cases appear to require a significant amount of time for recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Cuatro de los pacientes presentados la tuvieron. Pero también se han descrito meningoencefalitis, mielitis, lesiones del tronco simpático (síndrome de Horner), accidentes cerebrovasculares secundarios a vasculopatía cerebral… y la posibilidad de un síndrome de secreción inadecuada de hormona antidiurética [50]. Entre las secuelas destaca la neuralgia postherpética o neuralgia geniculada, desencadenada por el nervio intermedio de Wrisberg del VII, que recoge información sensitiva del oído (área de Hunt: región timpánica y CAE), parasimpática de las glándulas salivales y lacrimales, y sensorial de los 2 tercios anteriores de la lengua [51].…”
Section: Complicacionesunclassified